Comparing predictors of permanent pacemaker insertion after TAVR in new-generation versus early generation heart valves. (14th October 2021) - Gupta, R; Mahajan, S; Malik, A; Mehta, S; Patel, N
Abstract: Introduction: Transcatheter Aortic Valve Replacement (TAVR) has emerged as the standard of care for patient with severe aortic stenosis. Conduction abnormalities leading to permanent pacemaker (PPM) implantation is one of the most common complication after TAVR. Newer generation valves (NGV) such as Sapien S3, XT and Evolut are widely being used in real time practice. The aim of this analysis is to compare the predictors associated with increased risk of PPM implantation after TAVR in newer generation valves (NGV) as compared to older generation valves (OGV). Methods: A comprehensive literature search was performed in PubMed, Embase, and Cochrane to identify relevant trials. Summary effects were calculated using a DerSimonian and Laird random-effects model as odds ratio with 95% confidence intervals for all the clinical endpoints. Results: 18 observational studies with 16, 004 patients were identified. The incidence of PPM implantation after TAVR in our analysis was 8.9%. For the NGV, right bundle branch block (RBBB) and atrioventricular (AV) block were independent predictors of PPM insertion after TAVR. Baseline heart rate, presence of atrial fibrillation, and baseline intraventricular conduction delay were not significant predictors. However, for the OGV, risk of PPM implantation after TAVR was higher in presence of RBBB, depth of implant, valve size/annulus size, presence of atrial fibrillation and post-procedure AV block. Conclusions: Our analysis identified 2 factors that were significantly associated with increased risk of PPM insertion after TAVR in NGV compared to 6 factors with OGV. With the increasing physician expertise with TAVI and use of NGV, the incidence of post TAVR PPM insertion has reduced but baseline RBBB and AV conduction block still continue to be significant predictors of increased PPM insertion after TAVR. Funding Acknowledgement: Type of funding sources: None.